Lepton flavor violating decays of vector mesons; Physical Review D; Vol. 81, iss. 3 - Gutsche T. Thomas; Helo J. C. Juan C.; Kovalenko S. Sergey; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich (2010, 2010)
Title screen